Disaggregated Space System Concept Optimization: Model‐Based Conceptual Design Methods. Issue 6 (November 2015) - Thompson, Robert E.; Colombi, John M.; Black, Jonathan; Ayres, Bradley J.
ABSTRACT: Optimal design techniques have proven to be an effective systems engineering tool. Using systems architecture as the foundation, this paper explores the use of mixed variable optimization models for synthesizing and evaluating disaggregated space system concepts. Model‐based conceptual design (MBCD) techniques are used to identify and assess system architectures based upon estimated system cost and performance trades. The Disaggregated Integral System Concept Optimization (DISCO) methodology is introduced, and then applied to a space‐based, fire detection mission. Several results are obtained that indicate potential cost effectiveness gains from the concept design optimization of a fire detection mission. The general methodology has broad applicability for MBCD of systems, but is particularly useful for dynamic, nonlinear disaggregated space systems.